It is Time to Thoroughly Study the Effects of Mild Stress in Rodents, but also in Human Beings - Éric Le Bourg (SAGE Publishing, 2010)
Many experiments on the effect of mild stress on aging have been done in invertebrates, but not in mammals. Using mild stress to improve healthspan seems to be possible, because the few studies on humans which have been published appear to be promising. Particularly, one may wonder whether heat shocks could be of some use in therapy or as an integrated part of daily life of elderly people. However, the top priority is probably to study more thoroughly the effects of mild stress in rodents, and not only in invertebrates.